Analisis Perhitungan Aktuaria Dana Pensiun Menggunakan Metode Projected Unit Credit - Putriyana Nursal; Devni Prima Sari (Journal of Mathematics UNP, 2023)
The retired fund program is a program created by the government to ensure the needs and welfare of workers in old age, one of which is government employees. The problem of retired government employees in Indonesia is one of the burdens for the government, this is because retired funds are carried out using a pay as you go system. Retired fund management can also be managed using a fully funded system, where the implementation of a fully funded system can be carried out using the Projected Unit Credit Constant Dollar and Constant Percent methods. The calculation results show that the normal contribution using the Constant Percent method has increased significantly before entering retirement age compared to the Constant Dollar method. The amount of actuarial obligation using the Constant Dollar method is greater than using the Constant Percent method. Retired benefits obtained by retirees using the Constant Dollar method are greater than the Constant Percent method.